Synthesis of Camelina oil ethyl esters as components of jet fuels - Boichenko, Sergii; Zubenko, Stepan; Konovalov, Sergii; Yakovlieva, Anna (Eastern-European Journal of Enterprise Technologies, 2020)
Unrefined Camelina oil was transesterified on an alkaline catalyst with the application of commercial fuel ethanol of high hygroscopicity. It was shown that the rise of moisture content in alcohol up to 1 % leads to the low output of ethyl esters. The technological scheme of production of a pilot batch of Camelina oil ethyl esters in laboratory conditions was proposed. The scheme includes: preparation of catalyst solution, transesterification of oil with ethanol, sedimentation, alcohol stripping, separation, washing, drying and filtration. This allows obtaining products with the content of esters of about 92–93.5 %. The chromatographic analysis of the products of Camelina oil transesterification was done. The obtained products contain mostly unsaturated esters of fatty acids with the carbon chain length of 18 atoms. The comparative analysis of the fatty acid composition of the obtained ethyl esters of Camelina oil and ethyl esters of rapeseed oil, studied during previous researches of the authors, was done. The fatty acid composition allows forecasting lower viscosity, pour and freezing point of Camelina ethyl esters compared to rapeseed oil ethyl esters. The proposed assumption was proved by experimental data of researches of the basic physical-chemical characteristics of methyl and ethyl esters of rapeseed and camelina oils. The obtained experimental data proves the perspectiveness of using products of Camelina oil transesterification as components of jet fuels. In the future, compounding of synthesized fatty acid ethyl esters of Camelina oil with jet fuels will allow obtaining biofuels with improved quality parameters compared to biofuels with rapeseed oil esters